2022
DOI: 10.1002/aepp.13319
|View full text |Cite
|
Sign up to set email alerts
|

Choice effects associated with banning the word “meat” on alternative protein labels

Abstract: There is debate about whether meat labeling regulations might prevent consumer confusion or simply reduce the substitution between competing products. Using a between‐subjects experiment with a sample of 1504 U.S. households, we tested whether U.S. consumers could accurately identify the nutrition content and ingredients in traditional and nontraditional meat. We then conducted a discrete choice experiment to test for likely changes in choices between traditional and nontraditional meat products. Results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…We analyzed all top preceding label terms (e.g., cultured, cultivated, cell-cultured) with and without the term meat. Previous research has shown that inclusion of the word meat does not play a significant role in consumer understanding (47). However, identifying these products as meat has implications for the standards of identity for meat and meat products as outlined in the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed all top preceding label terms (e.g., cultured, cultivated, cell-cultured) with and without the term meat. Previous research has shown that inclusion of the word meat does not play a significant role in consumer understanding (47). However, identifying these products as meat has implications for the standards of identity for meat and meat products as outlined in the introduction.…”
Section: Discussionmentioning
confidence: 99%